Photo-reversible solid to liquid transition of azobenzene containing polymers: Impact of the chemical structure and chain length. (5th July 2022) - Pessoni, Laurence; Siniscalco, David; Boussonnière, Anne; Castanet, Anne-Sophie; Billon, Laurent; Delorme, Nicolas
Graphical abstract: Highlights: Synthesis of a series of azomonomers and their polymerization by Nitroxide Mediated Polymerization (NMP). Reversible photoisomerization and stability behavior in solution. Study of the reversible solid-to-liquid properties of azopolymers. Impact of molecular structure and molecular weight on the reversible photo-liquefaction process. Abstract: Azobenzene-containing polymers (azopolymers) can exhibit a photo-reversible solid to liquid transition which is illustrated by a cyclic softening and hardening of the polymer material upon irradiation. In order to understand the structure–property relationship on this transition, Nitroxide Mediated Polymerization (NMP) was used for the first time to synthesize a series of azopolymers. Four azopolymers bearing various azobenzene groups were designed with different molecular weights. Photo-isomerization properties and photo-reversible solid-to-liquid transitions were studied as function of the molecular weight and structure of the azopolymers. It was found that molecular weights and chemical structure of the azopolymer have both an impact on the features of the reversible solid-to-liquid transition. In particular, the higher the length of the substituent or the linker, the faster the transition. The results obtained in this study help on the one hand to better understand the mechanism of the photo-reversible solid-to-liquid transition and on the other hand to consider the design of novel azopolymers for many applications.